Ultraviolet Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry for Phosphopeptide Analysis with a Solidified Ionic Liquid Matrix. Issue 2 (April 2015) - Mukherjee, Gargee; Röwer, Claudia; Koy, Cornelia; Protzel, Chris; Lorenz, Peter; Thiesen, Hans-Jürgen; Hakenberg, Oliver W.; Glocker, Michael O.
A solidified ionic liquid matrix (SILM) consisting of 3-aminoquinoline, α -cyano-4-hydroxycinnamic acid and ammonium dihydrogen phosphate combines the benefits of liquid and solid MALDI matrices and proves to be well suitable for phosphopeptide analysis using MALDI-MS in the low femtomole range. Desalting and buffer exchange that typically follow after phosphopeptide elution from metal oxide affinity chromatography (MOAC) materials can be omitted. Shifting the pH from acidic to basic during target preparation causes slow matrix crystallization and homogeneous embedding of the analyte molecules, forming a uniform preparation from which (phospho) peptides can be ionized in high yields over long periods of time. The novel combination of MOAC-based phosphopeptide enrichment with SILM preparation has been developed with commercially available standard phosphopeptides and with α -casein as phosphorylated standard protein. The applicability of the streamlined phosphopeptide analysis procedure to cell biological and clinical samples has been tested (i) using affinity-enriched endogenous TRIM28 from cell cultures and (ii) by analysis of a two-dimensional gel-separated protein spot from a bladder cancer sample.